Livestock genomics for developing countries - African examples in practice - Marshall, Karen; Gibson, John P.; Okeyo Mwai, Ally; Mwacharo, Joram M.; Haile, Aynalem; Getachew, Tesfaye; Mrode, Raphael A.; Kemp, Stephen J. (Frontiers Media, 2019)
African livestock breeds are numerous and diverse, and typically well adapted to the harsh environment conditions under which they perform. They have been used over centuries to provide livelihoods as well as food and nutritional security. However African livestock systems are dynamic, with increased access to inputs such as animal feed and health-care, as well as markets, resulting in various levels of system intensification. In these systems the women and men livestock keepers are often seeking new livestock breeds or genotypes – typically those that increase household income through having enhanced productivity in comparison to traditional breeds whilst maintaining adaptedness. In recent years genomic approaches have started to be utilized in the identification and development of such breeds, and in this article we describe a number of examples to this end from sub-Saharan Africa. These comprise case studies on: (a) dairy cattle in Kenya and Senegal, as well as sheep in Ethiopia, where genomic approaches aided the identification of the most appropriate breed-type for the local productions systems; (b) a cross-breeding program for dairy cattle in East Africa incorporating genomic selection as well as other applications of genomics; (c) ongoing work towards creating a new cattle breed for East Africa that is both productive and resistant to trypanosomiasis; and (d) the use of African cattle as resource populations to identify genomic variants of economic or ecological significance, including a specific case where the discovery data was from a community based breeding program for small ruminants in Ethiopia. Lessons learnt from the various case studies are highlighted, and the concluding section of the paper gives recommendations for African livestock systems to increasingly capitalize on genomic technologies.